2005
DOI: 10.1002/mnfr.200400100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of glucose-lysineversus glucose-methionine Maillard reaction products consumption:in vitro andin vivo calcium availability

Abstract: The influence of glucose-lysine and glucose-methionine Maillard reaction products (MRPs) on calcium availability was studied in rats and in Caco-2 cells. Equimolar glucose/lysine and glucose/methionine mixtures (40% moisture) were heated (150 degrees C, 30 or 90 min) to prepare samples (GL30, GL90, GM30, and GM90, respectively). For 21 days, the rats were fed the AIN-93G diet (control group) or diets containing separately 3% of the heated mixtures (GL30, GL90, GM30, and GM90 groups, respectively). In the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…On formation of the complex, dietary mineral availability could be affected. In previous studies, using the rat as the animal model, we have demonstrated the relationship between MRP and calcium,7 magnesium8 and zinc metabolism 9…”
Section: Introductionmentioning
confidence: 98%
“…On formation of the complex, dietary mineral availability could be affected. In previous studies, using the rat as the animal model, we have demonstrated the relationship between MRP and calcium,7 magnesium8 and zinc metabolism 9…”
Section: Introductionmentioning
confidence: 98%
“…Besides the changes they provoke in protein availability, MRP may behave as chelating agents for metal cations, forming soluble and insoluble complexes that can affect mineral bioavailability (Friedman, 1996). The effects of MRP on calcium bioavailability have been studied using model systems from sugar-amino acids (Delgado-Andrade et al, 2005, 2006 or sugar-proteins (Seiquer et al, 2001) and in browned diets (Mesías et al, 2009). However, the effects of MRP derived from milk-overheat treatment on calcium metabolism have been scarcely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several other cellular effects of Maillard products and melanoidins have been observed in vitro, which may be linked to the physiological activity of processed food. Among those is the inhibition of angiotensin-I converting enzyme [15], influence on calcium bioavailability [16], or anti-bacterial activity [17]. The effects, however, were rarely related to defined structures, but rather to crude reaction mixtures or melanoidins, that are difficult to characterize.…”
Section: Introductionmentioning
confidence: 98%